Mesoporous Ceria Catalyst Synthesis: Effects of Composition on Thermal Stability and Oxygen Depletion in Methane Rich and Lean Environments - Di Nardo, Thomas (Université d'Ottawa / University of Ottawa, 2013)
This work takes a closer look at ceria catalyst synthesis through micelle self-assembly. We compare surfactants, precursors, solvent systems, and doping. The surfactants are the building blocks upon which the ceria can crystallize. The samples are calcinated to test their thermal stability. Characterization is performed using pXRD as well as physisorption. The samples that exhibited a higher thermal stability were characterized to have a high surface area as well as low fluctuations in crystallite size, pore volume, and pore size. Ceria synthesized with cerium (III) nitrate hexahydrate and CTAB in a water:ethanol mixture using sodium hydroxide showed to be the most effective at providing a thermally stable product. Doping the catalyst with titanium increased the thermal stability significantly. Select samples were run in a variety of fuel to oxygen ratios to determine the best conditions in which we could perform partial methane oxidation to recuperate hydrogen gas. Most of the experiments show oxygen depletion with minor changes in other gas levels indicating that there is no oxidation occurring. Curiously the oxygen levels do decrease. There is a possibility that there is a reaction occurring initially at room temperature and being exacerbated with further temperature increase.
Keywords: ceria; methane oxidation; oxygen depletion